2020
DOI: 10.1175/mwr-d-19-0414.1
|View full text |Cite
|
Sign up to set email alerts
|

The Amazonian Low-Level Jet and Its Connection to Convective Cloud Propagation and Evolution

Abstract: We describe the existence of an Amazonian low-level jet (ALLJ) that can affect the propagation and life cycle of convective systems from the northeast coast of South America into central Amazonia. Horizontal winds from reanalysis were analyzed during March, April, and May (MAM) of the two years (2014–2015) of the GoAmazon2014/5 field campaign. Convective system tracking was performed using GOES-13 infrared imagery and classified into days with high and weak convective activity. TheMAMaverage winds show a noctu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 56 publications
5
14
0
6
Order By: Relevance
“…On ShCu days, easterlies are stronger in the boundary layer in the early morning, and become weaker at levels between 850 and 750 hPa in the afternoon when compared to Deep days (Figure 7c). The low-level easterly wind enhancement is consistent with the observation that the Amazonian nocturnal low-level jet is stronger when it reaches T3 (in the morning hours because of the time for the signal to propagate from the coast) on days that are less convectively active over the Amazon (Anselmo et al, 2020). There are also significant differences in the large-scale subsidence, which is stronger on ShCu days, especially in the afternoon and early evening (Figures 7b and 7d).…”
Section: Large-scale Wind and Wind Shearsupporting
confidence: 87%
“…On ShCu days, easterlies are stronger in the boundary layer in the early morning, and become weaker at levels between 850 and 750 hPa in the afternoon when compared to Deep days (Figure 7c). The low-level easterly wind enhancement is consistent with the observation that the Amazonian nocturnal low-level jet is stronger when it reaches T3 (in the morning hours because of the time for the signal to propagate from the coast) on days that are less convectively active over the Amazon (Anselmo et al, 2020). There are also significant differences in the large-scale subsidence, which is stronger on ShCu days, especially in the afternoon and early evening (Figures 7b and 7d).…”
Section: Large-scale Wind and Wind Shearsupporting
confidence: 87%
“…Using the AMCs dataset in this study jointly with the atmospheric flow as seen by reanalysis and the soundings during GoAmazon2014, Anselmo et al . (2020) showed that there is the impact of the nocturnal Amazonian low‐level jet (ALLJ) on the propagation and life cycle of convective systems from the northeast coast of South America into central Amazonia. The ALLJ can act in different ways to produce the observed break and reactivation of the convection, as for instance by advection of humidity from the coast overnight that assists daytime convection the next day or by association with internal gravity waves that can propagate as described by Sun and Orlanski (1981).…”
Section: Resultsmentioning
confidence: 99%
“…Amazonian mesoscale convective systems (AMCSs) are defined in this study as a general descriptor of organized convective cloud clusters observed in the Amazon basin and neighbouring regions, including the coast. AMCS propagation and evolution is complex and depends on several factors, such as the large‐scale circulation, topography, and river and sea breezes (e.g., Oliveira and Fitzjarrald, 1993; Cohen et al ., 1995; Anselmo et al ., 2020). For example, satellite studies generally report a predominantly westward propagation of convective systems across the Amazon basin associated with the easterly trade winds (e.g., Machado et al ., 1998; Rehbein et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Montini et al (2019) discussed the better performance of the ERA-Interim compared with other reanalyzes to represent a vertical structure of the South American low-level jet. In addition, Anselmo et al (2020) found minor differences between the ERA-Interim and a modern and finer resolution reanalysis (MERRA-2) to reproduce a vertical structure of the low-level jet in the Amazon. They showed that the MERRA-2 low-level jet has a time of occurrence and vertical structure (with maximum wind speeds at 950 hPa) similar to local sounding observations, although it underestimates the wind intensity.…”
Section: Datamentioning
confidence: 92%